Population Screening for Breast Cancer (The Journal of Ad-din Women's Medical College, 2024)
Screening female population for breast cancer has a significant impact on survival rate. The quality of this screening service provided by the UK and other developed countries are improving continually, with increased sensitivity reducing rates of non-surgical diagnoses. The results of screening have exceeded the initial expectations of the service, where an improvement in disease-specific survival of 25% was anticipated. Virtually, to reduce the mortality of breast cancer up to 30-40%. We recommend that National Breast Cancer Screening Program should be launched in the developing nations also to rip benefits of screening.The Journal of Ad-din Women's Medical College; Vol. 12 (1), Jan 2024; p 39-43